2019
DOI: 10.1155/2019/9268179
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cognitive Function after Traumatic Brain Injury: A Clinical Trial on the Potential Use of the Semi-Immersive Virtual Reality

Abstract: Traumatic brain injury (TBI) is the most common cause of long-term disability and death among young adults, and it represents an enormous socioeconomic and healthcare burden. Our purpose is to evaluate the effects of a virtual reality training with BTs-Nirvana (BTs-N) on the recovery of cognitive functions in TBI subjects, using the interactive semi-immersive program. One hundred patients with TBI were enrolled in this study and randomized into either the Traditional Cognitive Rehabilitation Group (TCRG: n=50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 35 publications
1
41
0
4
Order By: Relevance
“…Significant improvements in learning following a VR exercise program are thought to be associated with changes in neuronal plasticity that enhance the working memory [ 139 ]. VR also significantly increases cognitive flexibility, shifting skills, and selective attention, leading to better behavioral outcomes in brain-injured patients [ 140 ]. Improvement in selective memory processes and problem-solving skills facilitate social reintegration and leads to better vocational outcomes [ 141 ].…”
Section: Virtual Reality For Neurorehabilitationmentioning
confidence: 99%
“…Significant improvements in learning following a VR exercise program are thought to be associated with changes in neuronal plasticity that enhance the working memory [ 139 ]. VR also significantly increases cognitive flexibility, shifting skills, and selective attention, leading to better behavioral outcomes in brain-injured patients [ 140 ]. Improvement in selective memory processes and problem-solving skills facilitate social reintegration and leads to better vocational outcomes [ 141 ].…”
Section: Virtual Reality For Neurorehabilitationmentioning
confidence: 99%
“…To stimulate our patient, we used the Nirvana system, which creates a VR semi-immersive environment, allowing to observe a three-dimensional scene projected on a screen: the playful environment could increase patient’s compliance, amplifying the effects of the rehabilitation treatment tailored to the actual needs of the patients [ 31 , 66 , 67 ]. Various studies have shown that VR activates different perceptual and experiential aspects, with the stimulation of multiple perceptual channels, thanks to the use of auditory and visual feedback [ 13 , 14 , 32 , 33 ]. This complex sensory stimulation may increase the patient’s awareness of his/her performance, inducing changes in neural plasticity processes [ 13 , 14 , 56 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the identification of spatially and temporally distributed brain responses, which are unlikely when awareness is not present or not entrained [ 74 ]. Therefore, these indices may be useful to evaluate adequately motor-cognitive outcomes (with particular regard to anchoring and visual), and to monitor EEG responsiveness to a task (sensorimotor rhythms reshape) even in a VR environment, where it is suggested that the patient could be more stimulated [ 13 , 14 , 32 , 33 ]. In the current literature, two studies integrated VR with ERPs on patients with DoC by using the Neurowave (Khymeia SRL; Padua, Italy) a technologically advanced device that allows the automated programming and administration of sensory stimuli and the simultaneous monitoring of multiple biophysiological signals [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Weigl has been used with patients with a range of aetiologies, including stroke (Chan et al, 2017;Gregoire et al, 2013;Leeds et al, 2001), traumatic brain injury (Baird et al, 2005;De Luca et al, 2019), dementia (Byrne-Davis et al, 1998;Chiu et al, 2012;Tian et al, 2003), Parkinson's disease (Hobson et al, 2007), psychiatric illness (Tamkin, 1980;Tamkin & Kunce, 1982;Tamkin et al, 1984), and alcoholism (Tamkin & Dolenz, 1991). However, few studies have investigated the performance of patients with focal lesions.…”
Section: Introductionmentioning
confidence: 99%